Pengaruh Brand Ambassador, Brand Image, dan Word of Mouth Terhadap Keputusan Pembelian - Willa Tiara Amalia; Alimuddin Rizal Riva’i (UNESA In Collaboration With APSMBI (Aliansi Program Studi dan Bisnis Indonesia), 2022)
This study aims to examine and analyze the influence of brand ambassadors, brand image, and word of mouth on purchasing decisions. The population in this study were prospective consumers of Lemonilo products. The researchers took a sample of 75 respondents using a purposive sampling technique with the criteria of respondents being people who would make purchasing decisions for Lemonilo products. With the help of the SPSS version 26.0 program, the relationship between variables can be identified using multiple linear regression analysis. The results obtained from this study indicate that brand ambassadors has a positive regression coefficient value and significant on purchasing decisions, brand image has positive regression coefficient value and significant on purchasing decisions, and word of mouth has a positive regression coefficient value and significant on purchasing decisions.